2010
DOI: 10.1210/en.2010-0138
|View full text |Cite
|
Sign up to set email alerts
|

3β-Hydroxysteroid Dehydrogenase Is a Possible Pharmacological Target in the Treatment of Castration-Resistant Prostate Cancer

Abstract: Prostate cancer usually responds to androgen deprivation therapy, although the response in metastatic disease is almost always transient and tumors eventually progress as castration-resistant prostate cancer (CRPC). CRPC continues to be driven by testosterone or dihydrotestosterone from intratumoral metabolism of 19-carbon adrenal steroids from circulation, and/or de novo intratumoral steroidogenesis. Both mechanisms require 3beta-hydroxysteroid dehydrogenase (3betaHSD) metabolism of Delta(5)-steroids, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 20 publications
(31 reference statements)
2
60
0
Order By: Relevance
“…These results suggest that DHEAS undergoes metabolism at least to DHEA, mediated by STS. DHEA thus generated may have a weak androgenic potential to activate AR directly, but is more likely converted to T or DHT via 3b-hydroxysteroid dehydrogenase (3bHSD), since cell proliferation of LNCaP cells in the presence of DHEA was reported to be suppressed by inhibition of 3bHSD [15]. Although DHEA is present in human serum (~ 5 nM), the DHEAS concentration in serum (3 ~ 5 μM) is almost a thousand fold greater [12]; therefore, DHEAS may be taken up by prostate cancer cells via OATPs as a source of DHEA to compensate for the shortage of androgen in serum.…”
Section: Contribution Of Oatp1a2 To Dheas-induced Cell Growth In Lncamentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that DHEAS undergoes metabolism at least to DHEA, mediated by STS. DHEA thus generated may have a weak androgenic potential to activate AR directly, but is more likely converted to T or DHT via 3b-hydroxysteroid dehydrogenase (3bHSD), since cell proliferation of LNCaP cells in the presence of DHEA was reported to be suppressed by inhibition of 3bHSD [15]. Although DHEA is present in human serum (~ 5 nM), the DHEAS concentration in serum (3 ~ 5 μM) is almost a thousand fold greater [12]; therefore, DHEAS may be taken up by prostate cancer cells via OATPs as a source of DHEA to compensate for the shortage of androgen in serum.…”
Section: Contribution Of Oatp1a2 To Dheas-induced Cell Growth In Lncamentioning
confidence: 99%
“…DHEAS is a thousand fold more abundant than testosterone in human serum [12], and is essentially unaffected by ADT. DHEAS is hydrolyzed to DHEA by STS [13], and DHEA can be converted to androstenedione in prostate cancer [14], resulting in activation of AR function [15]. More recently, clinical observations have suggested that several OATPs are upregulated in castration-resistant metastatic prostate tumor tissues derived from human patients [16]; however, it remains unclear whether OATPs play a role in prostate cancer cell survival under androgen-depleted conditions.…”
Section: Introductionmentioning
confidence: 99%
“…DHT synthesis, either from adrenal precursors or via intratumoral de novo steroidogenesis from cholesterol, requires 3b-hydroxysteroid dehydrogenase/isomerase (3bHSD) enzymatic activity (16)(17)(18). Dehydroepiandrosterone (DHEA) and abi have structural similarities, in that both have a 3b-hydroxyl, D 5 -19-carbon steroid nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors of 3β-HSD have been explored as an androgen deprivation technique as they are effective in decreasing proliferation in androgen-sensitive LNCaP or CRPC cell lines 22Rv1, VCaP and PC346C in vitro (Evaul et al 2010, Kumagai et al 2013. Furthermore, abiraterone was found to inhibit 3β-HSD activity in addition to CYP17A1 in prostate cancer cell lines and isolated yeast microsomes (Li et al 2012).…”
Section: :6mentioning
confidence: 99%